2019
DOI: 10.18615/anadolu.660303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some Quality Characteristics in Durum Wheat (Triticum durum L.) Genotypes Grown under Rainfed and Irrigated Conditions by Mixograph Device

Abstract: In this study some quality characteristics and mixograph parameters of some durum wheat (Triticum durum L.) varieties and advanced lines were investigated and the relationship between them was determined. The material used in the study was grown in rainfed and irrigated conditions in 2016-2017 growing period at Bahri Dağdaş International Agricultural Research Institute. Some physical, chemical and rheological properties of durum wheat samples as well as some mixograph parameters (peak time (PT), peak height (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Mixograph development time ranged between 1.55 and 3.67 min in terms of location means. In parallel study, similar results were obtained and it was determined that the mixograph development time of some durum wheat ranged between 1.54 and 3.77 minutes (Demir et al, 2019). Line 7 (3.79 min) had the highest value in examined lines and Eminbey (3.67 min) had the highest value in examined varieties (Table 3).…”
Section: Semolina Color (B)supporting
confidence: 66%
See 1 more Smart Citation
“…Mixograph development time ranged between 1.55 and 3.67 min in terms of location means. In parallel study, similar results were obtained and it was determined that the mixograph development time of some durum wheat ranged between 1.54 and 3.77 minutes (Demir et al, 2019). Line 7 (3.79 min) had the highest value in examined lines and Eminbey (3.67 min) had the highest value in examined varieties (Table 3).…”
Section: Semolina Color (B)supporting
confidence: 66%
“…Aydoğan et al (2012) found that the mean protein content of 5 durum wheat varieties was 13.89% in irrigated conditions during 2009-2011. In a similar study, the average protein content of 9 different durum wheat was 12.57% (Demir et al, 2019). SDS sedimentation: SDS sedimentation (SDSS) is an important parameter that gives an idea about gluten strength in durum wheat quality breeding (Brites and Carrillo, 2001).…”
Section: Resultsmentioning
confidence: 91%